2010
DOI: 10.1097/aud.0b013e3181e5d1a7
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Speech Discrimination in 4- to 7-Yr-Old Children as Indexed by Event-Related Potential Mismatch Responses

Abstract: Maturation of speech discrimination, as indexed by MMN, occurs more rapidly between 4 and 7 yrs of age for vowels than for tones. A p-MMR preceding the MMN also reflects discrimination in younger children and declines in amplitude with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 66 publications
7
106
3
2
Order By: Relevance
“…It is noteworthy that the individual MMN analysis adopted in the present study is crucial for the purposes of clinical application and longitudinal follow up comparison 19 in children with CIs, even though it is likely to increase the possibility of false positive or negative rates (29). Previous studies have suggested that MMN group average method would improve the signal-to-noise and consequently provide clear MMN responses (17,23,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the individual MMN analysis adopted in the present study is crucial for the purposes of clinical application and longitudinal follow up comparison 19 in children with CIs, even though it is likely to increase the possibility of false positive or negative rates (29). Previous studies have suggested that MMN group average method would improve the signal-to-noise and consequently provide clear MMN responses (17,23,28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the MMN amplitude did not differ significantly among the different age groups of children with normal hearing. For example, studies by Shafer et al [19] and Morr et al…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies have used MMN to assess speech sound perception (Lovio et al, 2009;Shafer et al, 2010;Partanen et al, 2011). Deficits in speech sound processing, such as impairment in discrimination of vowels or syllables, and in differentiation of sound frequency or duration, are hallmarks of language impairment, dyslexia, and reading problems (Bishop, 2007;Sharma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kraus et al (1996) Há muitos conflitos na literatura sobre a maturação do MMN com relação à latência e à amplitude (Alho et al, 1990;Morr et al, 2002). Apesar disso, a maioria dos estudos mostram que crianças a partir de 4 anos de idade apresentam um MMN consistente e robusto (Shafer et al, 2000;Morr et al, 2002;Shafer et al, 2010). Esses estudos também apontam uma correlação negativa entre a latência do MMN e a idade dos indivíduos, com diminuição de latência de 11ms/ano para tons (Shafer et al, 2000;Morr et al, 2002) e de 25ms/ano para sons de fala (Shafer et al, 2010).…”
Section: Várias Regiões Corticais Têm Sido Identificadas Como Geradorunclassified